Herança + O Fabuloso Inventário das Obras do Meu Avô:: a cidade como legado da arte de construir - Pereira, Gabriela Leandro; Pereira, Mariana Leandro (Farol, 2023)
Since the installation“Herança + O Fabuloso Inventário das Obras do Meu Avô”, mounted at the 13th International Architecture Biennial of São Paulo (2022), this article seeks to offer a provocation about the invisibility of construction workers in the debate, in the historiography , in memory and in the curatorship of architecture and urbanism. Starting from the intertwined relationship between life, work and the art of building, the granddaughter-authors mobilized research, family archives and institutional documents to shape the installation.